2008
DOI: 10.1002/cncr.23501
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary diffuse gastric cancer

Abstract: Introduction: The objective of this study was to identify the pattern of neurological deficits and document electrophysiological changes in women with macromastia. Methods: Patients with macromastia and neurological complaints underwent clinical evaluation and electrodiagnostic (EDx) studies of the upper limbs. Results: Findings include low‐amplitude medial antebrachial cutaneous (MACN) sensory nerve action potentials (SNAPs) and median compound muscle action potentials (CMAPs) and chronic denervation changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…The carcinogenic mechanism in this case might be different from that observed in typical multiple EGCs, since the clinicopathological characteristics were completely different. Lynch et al 13 and Rogers et al 14 reported hereditary diffuse gastric cancers, in which a germ-line mutation resulted in multiple signet-ring cell carcinomas similar to those observed in the present case. Such germ-line mutations might be associated with the pathogenesis of the present case.…”
Section: Discussionsupporting
confidence: 84%
“…The carcinogenic mechanism in this case might be different from that observed in typical multiple EGCs, since the clinicopathological characteristics were completely different. Lynch et al 13 and Rogers et al 14 reported hereditary diffuse gastric cancers, in which a germ-line mutation resulted in multiple signet-ring cell carcinomas similar to those observed in the present case. Such germ-line mutations might be associated with the pathogenesis of the present case.…”
Section: Discussionsupporting
confidence: 84%
“…The missense variant 6571G[C (E2175Q) in exon 11 was identified in family 25-7-000059 with 2 affected PC patients (ages 43 and 52 years) and 1 one affected member with breast cancer (age 61 years). This mutation is not yet listed in the Breast Cancer Information Core (BIC), but was recently identified in a patient with a family history of breast and ovarian cancer who was suffering from both breast and diffuse gastric cancer [25]. Since we had germline DNA from only one affected individual, we could not analyze segregation of this BRCA2 variant with the disease.…”
Section: Brca2 Mutation Analysismentioning
confidence: 96%
“…Gastric acid and enzymes plays a key role in the digestive procedure. Increasing evidence indicating that factors inhibiting the acid secretion are involved in the carcinogenesis of gastric cancer (Louise et al 2005;Argani et al 2007;Vilkin et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Despite some advances were achieved in the treatment of advanced gastric cancer (Sipponen 2002;Fukase et al 2008;Lee et al 2008;Sugano 2008), these patients still do poorly. Radical surgical resection is still the best treatment option in clinical practice (Lynch et al 2008). Overall survival of patients with gastric cancer remains disappointing.…”
Section: Discussionmentioning
confidence: 99%